THE USE PICTURE WORD INDUCTIVE MODEL (PWIM) TO IMPROVE STUDENTS’ DESCRIPTIVE TEXT WRITING CLASS VII SMP NEGERI 3 KUTACANE ACADEMIC YEAR 2021/2022 - WIDYA HASNI; RAJA FAUZIAH; ABDUL HALIM (Tuwah Pande: Jurnal Ilmu Pendidikan dan Pengajaran, 2023)
Abstract. This study deals with the use picture word inductive model to improve students’ descriptive text writing class VII SMP Negeri 3 Kutacane Academic Year 2021/2022. Its objective is to find out whether the use picture word inductive model has a significance effect in writing descriptive text.Population used in this study of class VII were 87 and samples used in this study were 28 students. The method used in this study is an experimental method with a one group as pretest and posttest design .This study was carried on using quantitave method. The data was analysed by using t-test.The researcher found the pretest mean = 44,64 , deviation standard = 6,37 and experienced an increase in the posttest mean = 78,57 deviation standart = 4,05. From this analysis, writer found that guided picture word inductive model has significane in teaching writing descriptive text. It can be proved by the result of the analysis showed that “ ” observed about 23,73 was higher than “ttable” about 2,052 with the level significance is 0,05% it implies that the teacher of English should use picture word inductive model in teaching writing descriptive text so that the teaching and learning process can be successful.